Study on non-contact current path formation using charged particle beams. (September 2016) - Ma, J.; Fujimura, Y.; Utsumi, M.; Tomonaga, S.; Mashiko, Y.
Abstract: For measurement of electrical characteristics it is essential to supply an electrical current or apply a voltage to the circuit. This study have been carried in order to realize the creation of a stable electrical current flow in the microscopic region only by using the charged particle beams, without requiring contact of the mechanical probes. And it was revealed that stable and constant current flow can be achieved in a self-aligned current-controlling manner by utilizing the secondary electrons. We also have clarified that the mechanism of stabilizing current in a self-aligned manner is dependent on space charge limited current of secondary electrons. Highlights: This study has been carried to realize a non-contact probing technique for the failure analysis of microcircuits. A stable current flow creation in the microscopic region was realized only using the charged particle beams. The mechanism of stabilizing current is clarified to be due to space charge limited current of secondary electrons.